2021
DOI: 10.3390/foods10040745
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil Microcapsules as Omega-3 Enrichment Strategy: Changes in Volatile Compounds of Meat Products during Storage and Cooking

Abstract: This work aims to analyze the effects of processing and storage on the volatile compound profile of different meat products enriched in ω-3 polyunsaturated fatty acids (PUFA). Monolayered (Mo) and multilayered (Mu) microcapsules of fish oil were tested. The profiles of volatile compounds were analyzed by solid-phase microextraction (SPME) coupled with gas chromatography-mass spectrometry (GC-MS). The enrichment with Mo significantly increases the abundance of volatile compounds from lipid oxidation and markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Silva et al [ 2 ] aimed to investigate the impact of including a resveratrol complex as a functional ingredient to lemon juice, concluding that a complex made with maltodextrine promotes the solubility and antioxidant stability of reveratrol in lemon juices. In the studies of Solomando et al [ 8 , 9 ], who enriched the omega-3 fatty acids in different meat products (cooked and dry-cured sausages) by adding two types of fish oil microcapsules (monolayered and multilayered), the abundance of volatile compounds from lipid oxidation and markers of omega-3 oxidation was higher when adding monolayered microcapsules. Moreover, findings indicated that the changes in volatile compounds during storage depend on the type of fish oil microcapsules and the meat products, having an increased abundance of omega-3 oxidation markers in dry-cured sausages added with monolayered microcapsules.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Silva et al [ 2 ] aimed to investigate the impact of including a resveratrol complex as a functional ingredient to lemon juice, concluding that a complex made with maltodextrine promotes the solubility and antioxidant stability of reveratrol in lemon juices. In the studies of Solomando et al [ 8 , 9 ], who enriched the omega-3 fatty acids in different meat products (cooked and dry-cured sausages) by adding two types of fish oil microcapsules (monolayered and multilayered), the abundance of volatile compounds from lipid oxidation and markers of omega-3 oxidation was higher when adding monolayered microcapsules. Moreover, findings indicated that the changes in volatile compounds during storage depend on the type of fish oil microcapsules and the meat products, having an increased abundance of omega-3 oxidation markers in dry-cured sausages added with monolayered microcapsules.…”
mentioning
confidence: 99%
“…Regarding the encapsulation techniques used in the works published in this special issue, spray-drying has been the most applied one. It has been used to form microcapsules of astaxanthin [ 5 ], hempseed oil [ 7 ], fish oil [ 8 , 9 ], tangereting [ 10 ] and vanilla [ 11 ] from emulsions previously prepared. For astaxanthin and tangereting, the oil phase of emulsions was prepared with sunflower and bergamot oil, respectively [ 5 , 15 ], whereas an oleoresin extraction was carried out in the case of vanilla [ 11 ].…”
mentioning
confidence: 99%
See 3 more Smart Citations